The Adaptation of Early Childhood Care and Education to Cultural and Local Characteristics in West Africa: Challenges for Educational Psychology Research - Kathrine Maleq; Magdalena Fuentes; Abdeljalil Akkari (Foxton Books, 2022)
This critical review aims to question whether or not the enthusiasm around early childhood care and education (ECCE) programmes is producing premature models, ill-adapted to West African socio-cultural contexts. Reviewing research that investigates the impact of ECCE on cognitive development and school readiness, we first focus on the universal valuing of formal ECCE, supported by both scientific research and international education agendas. Second, we present a classification that provides a framework to grasp the multiplicity of ECCE programmes and models across West African countries and their relevance to local contexts. Based on the literature reviewed, we conceptualise a multilevel model of ECCE within a holistic and ecologic approach. In the third part, we present research that underlines the challenges for educators and their central role in the design of culturally relevant ECCE. The fourth part will draw from research findings and stress the need to rethink appropriate methods and research tools to assess the quality and outcomes of ECCE programmes in West Africa. We conclude by proposing to move away from ECCE perspectives in which marginalised communities are perceived as deficient towards locally relevant and socially just models.